Pembinaan dan Pengembangan Tenaga Pendidik: Peran Manajemen dalam Peningkatan Kualitas Pendidikan Anak Usia Dini - Sri Widyawati; Ribut Wahyu Eryanti; Atok Miftachul Hudha (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2023)
This paper aims to describe the duties and functions of educator and education management which is one part of the eight national education standards. This study uses a qualitative research method of library research (library research). The results of this study indicate that the duties and functions of the management of educators and educational staff are carried out based on statutory regulations with the aim of improving the quality of national education, developing science, technology and the arts, as well as serving the community. The implementation of the tasks and functions of educator and education management consists of six components namely: (a) planning, (b) rehabilitation, (c) work placement, (d) compensation, (e) coaching and development, (f) evaluation. Management functions and mandates have implications for schools in addressing the shortage of educators and education personnel through recruitment. Coaching and development is also carried out through individual learning, training and further education, both carried out by working groups of teachers, schools and the education office.